Trauma-sensitive residential care: perspectives of Portuguese professionals to spark change - Negrão, Mariana (2024)
Despite global pressure for deinstitutionalization of children in care, and recent legislative changes, Portugal remains a country with very high prevalence of residential care amongst at-risk children. These children were exposed to multiple traumatic events that can disrupt development. Thus, the expansion toward a truly sensitive approach to trauma is valuable, as it aims to increase awareness of its effects and ensure the best empathic care, providing a safe and healthy environment, with consequences also for the wellbeing of residential care staff. The present study aims to characterize the quality of residential care environments in Portugal through the lens of trauma-sensitive care, and to map professionals understanding of main domains, priorities and obstacles to change in this area. The study adopts a mixed method design, reporting on the perceptions of 85 professionals. Main findings show that professionals demonstrate better perceptions regarding physical environment but consider training and supervision as fragile dimensions. Qualitative data bring detail to these views, reinforcing the call for training to all staff and for continuous support to demanding job roles. This exploratory study highlights major aspects that urge to ensure trauma-sensitive residential care – supportive of professionals, to meet the needs of children and youth.